Pengaruh Disiplin Belajar Terhadap Hasil Belajar Bahasa Indonesia Di Sekolah Dasar 97 Kabupaten Barru - Nurhaedah, Nurhaedah; Abdullah, Angriani; Afriati, Afriati; Zulkarnain, Zulkarnain; Nanang, Nanang; Alimuddin, Hadijah (Jurnal Ilmiah Amanah Akademika, 2021)
Learning disciplines have a profound effect on students' learning outcomes. One of the factors that influences learning outcomes is learning discipline. This research focuses on learning disciplines on the results of learning Indonesian grade III students of SDN 97 Barru Regency, because Indonesian is a definite science. So students tend to dislike Indonesian subjects and this can affect students' learning outcomes. This study is an ex post facto study, as there is no control over free variables and researchers do not conduct arrangements or manipulations of free variables. In this study consisted of two variables, namely one free variable and one bound variable. The free variable in this study is the learning discipline (X). While the bound variable is the result of learning Indonesian (Y). For sampling using saturated sampling techniques. Based on the results of the study and the results of the analysis can be known from the results of the hypothesis test calculation obtained tcount = 9,906 for variables (X) and (Y). Then look for ttable with α= 5%, dk= 33-2= 31, so that ttable is 1,696. Because tcount > ttable then Ha is accepted, if accepted then there is a disciplinary influence on the results of learning Indonesian students grade III SDN 97 Barru Regency.